For Deliberation Sake Show Some Constructive Emotion! How Different Types of Emotions Affect the Deliberative Quality of Interactive User Comments - Esau, Katharina; Wilms, Lena; Baleis, Janine; Keller, Birte (Javnost-The Public, 2023)
Deliberation is classically understood as a communication process where equal participants justify their positions in a respectful, reciprocal, argumentative manner. However, critical scholars have argued for a concept of deliberation that incorporates other forms of communication beyond argumentation, for example, expressions of emotions. While previous research focused on differences between positive and negative emotions, we introduce a distinction between constructive and non-constructive expressions of emotions. Whilst constructive emotions focus on the discussed issue, non-constructive emotions refer to other participants. We draw on a quantitative relational content analysis of user comments written in an online-participation platform. The results show a positive effect of constructive expressions of emotions on the deliberative quality of interactive user comments and a negative effect of non-constructive expressions of emotions. Overall, we conclude that emotions can promote the deliberative quality of interactive user comments if they are not focused on other participants but on the discussed issue.